2020
DOI: 10.1016/j.jbiotec.2019.11.014
|View full text |Cite|
|
Sign up to set email alerts
|

Mixtures of aromatic compounds induce ligninolytic gene expression in the wood-rotting fungus Dichomitus squalens

Abstract: Heterologous production of fungal ligninolytic cocktails is challenging due to the low yields of catalytically active lignin modifying peroxidases. Production using a natural system, such as a wood-rotting fungus, is a promising alternative if specific or preferential induction of the ligninolytic activities could be achieved. Using transcriptomics, gene expression of the white-rot Dichomitus squalens during growth on mixtures of aromatic compounds, with ring structures representing the two major lignin sub-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In situ expression and production of the D. squalens and P. ostreatus GH44 genes and proteins have been shown in previously published transcriptome and exoproteome datasets ( Daly et al, 2018 ; Wu et al., 2020 , 2021 ). In short, D. squalens CBS464.89 expressed xegA and produced the corresponding protein during growth on spruce and birch wood ( Daly et al, 2018 , 2020 ), whereas P. ostreatus PC9 expressed the XegA encoding gene on rice straw ( Wu et al., 2021 ), and in the Δ pex1 and Δ gat1 mutants on beechwood sawdust ( Wu et al., 2020 ), again supporting a role for these genes in plant biomass degradation. Therefore, these two candidates were selected for further characterization to demonstrate the function of basidiomycete GH44 enzymes.…”
Section: Resultsmentioning
confidence: 87%
“…In situ expression and production of the D. squalens and P. ostreatus GH44 genes and proteins have been shown in previously published transcriptome and exoproteome datasets ( Daly et al, 2018 ; Wu et al., 2020 , 2021 ). In short, D. squalens CBS464.89 expressed xegA and produced the corresponding protein during growth on spruce and birch wood ( Daly et al, 2018 , 2020 ), whereas P. ostreatus PC9 expressed the XegA encoding gene on rice straw ( Wu et al., 2021 ), and in the Δ pex1 and Δ gat1 mutants on beechwood sawdust ( Wu et al., 2020 ), again supporting a role for these genes in plant biomass degradation. Therefore, these two candidates were selected for further characterization to demonstrate the function of basidiomycete GH44 enzymes.…”
Section: Resultsmentioning
confidence: 87%
“…Plant biomass is recognized as a sustainable source of mixed sugars for fermentation to second generation biofuels and high-value molecules. Fungi have evolved different strategies to degrade lignocellulose [53][54][55][56][57][58]. The genome of the thermophilic fungus C. thermophilum suggested that this fungus should prefer to degrade monocots that are rich in cellulose, xylan and β-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…Each WRF can secrete a distinct type of LME depending on the species or even strain (Torres et al 2003 ; Wesenberg et al 2003 ; Levin et al 2004 ; Yang et al 2013b ; Kinnunen et al 2016 ). The enzymatic pathways of living WRF undergo the control of gene promoters, which are stimulated by an appropriate environmental factor (Suetomi et al 2015 ; Toyokawa et al 2016 ; Daly et al 2020 ). The triggering factor for LMEs is primarily the balance of nitrogen and carbon in the medium.…”
Section: Potential Of Wrf To Remove Bpa Bps and Np From Wastewatermentioning
confidence: 99%